Seismic Assessment of RC Building Using Pushover Analysis - Riza Ainul Hakim (International Journal of Engineering Science and Technology Development (IJEST), 2013)
Current research works indicated that parts of Kingdom of Saudi Arabia have low to moderate seismic regions. For structural engineers, seismic load should be considered as important aspect that needs to be included in the building design. However Major part of buildings are designed for gravity loading only and poorly detailed to accommodate lateral loads. The purpose of this paper is to investigated gravity supporting building its resistance to expected seismic loading in different regions (Makkah, Jeddah, Gizan and Haql). In this paper, a test RC building that was designed for gravity loading only is investigated. This will be accomplished by performing the nonlinear static analysis (pushover analysis) according to ATC 40. Pushover analysis produces the pushover curves, capacity spectrum, plastic hinges and performance level of the building. This analysis gives better understanding seismic performance of buildings and also traces the progression of damage or failure. The building performance level is determined by intersection of demand and capacity curves and the hinge developed in the beams and the columns. The results show that the test building is found inadequate for Haql region and it still can be considered for Makkah, Jeddah and Gizan.